Clinician wellbeing: The impact of supporting refugee and asylum seeker survivors of torture and trauma in the Australian context. (14th June 2019) - Posselt, Miriam; Deans, Carolyn; Baker, Amy; Procter, Nicholas
Abstract : Objective: Providing therapy to refugees and asylum seekers who have experienced torture and trauma exposes clinicians to traumatic stories. Additionally, clinicians working with refugees and asylum seekers are often required to work in the context of immigration detention and uncertainty for clients' futures, potentially compounding the already difficult nature of trauma therapy and further impacting clinician wellbeing. There is a paucity of research considering the consequences of working with refugees and asylum seekers, particularly in the Australian context. This mixed‐methods study aimed to explore the impact of working therapeutically with refugees and asylum seekers on the psychological wellbeing of Australian clinicians. Method: Fifty clinicians who work with refugees and asylum seekers participated in an online survey focussing on the impact of their work and protective factors. The survey also comprised open‐ended questions to collect qualitative information. Results: The sample reported low levels of depression, anxiety, stress, compassion fatigue, and average to high levels of compassion satisfaction. Analysis of free‐text comments regarding aspects of the job that impact wellbeing revealed three main themes: government and policy level stressors, work environment, and meaning‐making for the clinician. Conclusion: While the sample reported psychological wellness, qualitative responses revealed that Australian immigration policies impact clinician wellbeing to a greater extent than exposure to traumatic narratives. Engaging in meaning‐making processes regarding work appeared to positively impact clinician wellbeing. Those in leadership or supervisory positions would benefit from understanding what aspects of the work most significantly impact clinicians, in order to best support staff.